Adaptive Kalman snake for semi-autonomous 3D vessel tracking. Issue 1 (October 2015) - Lee, Sang-Hoon; Lee, Sanghoon
<x xml:space="preserve">Abstract</x> Highlights We propose 3D vessel segmentation and tracking algorithm based on an active contour model and a Kalman filter. To obtain refined segmentation results, we model an adaptive control spacing algorithm for the active contour model. To obtain refined tracking results, we model an initial contour estimation algorithm for the Kalman filter. ROC analyses demonstrated the time efficiency and tracking robustness of the proposed model. Processing time can be effectively reduced by approximately 20%.